Practices of Bsed English Students in Dealing With English Language Anxiety - Bolivar, Rheza Mae; Bayno, Maribel; Suarez, Aris Pet Angeli; Naparan, Genesis (Papanda Publisher, 2024)
This qualitative study investigates the practices of Bachelor of Secondary Education (BSED) English majors in dealing with English language anxiety. Through interviews with the eleven research participants, peers, and classmates, the study identifies triggers, manifestations, and coping strategies associated with language anxiety among BSED English students. Findings reveal that past negative experiences, fear of criticism, lack of confidence, and performance pressure contribute to language anxiety, manifested in various physical and emotional symptoms. Coping mechanisms include self-talk, self-acceptance, breathing techniques, and preparation, which highlight the importance of psychological and practical approaches in managing anxiety. The study concludes that language anxiety poses significant challenges for BSED English students but can be effectively managed through targeted interventions and support strategies. Recommendations include integrating anxiety-reduction techniques into teaching practices, providing opportunities for practice and feedback, fostering a supportive classroom atmosphere, offering mindfulness workshops, and conducting further research on effective interventions. Implementation of these recommendations can enhance students' academic performance and well-being, creating a more inclusive and supportive learning environment for English language learners.